Preparation of ultra-thin polypyrrole nanosheets decorated with Ag nanoparticles and their application in hydrogen peroxide detection - Mahmoudian, M.R.; Ebadi, M.; Basirun, Wan Jefrey; Alias, Y. (Elsevier, 2012)
This study examines the preparation of ultra-thin polypyrrole nanosheets decorated with Ag nanoparticles (Ag-UTPNSs) and their application in the enzyme-less detection of hydrogen peroxide (H2O2) detection. The X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) results confirmed that Ag nanoparticles (NPs) were deposited onto the surface of the UTPNSs. The increase of the H2O2 reduction current peak to 120 mu A in the presence of the Ag-UTPNS/glassy carbon electrode (GCE) as compared to the UTPNS/GCE indicates that the sensitivity of the electrode to H2O2 is significant. This observation can be explained by the larger surface area of the UTPNSs, which can increase the interactions between the polymer and the AgNO3 solution during the deposition of the Ag NPs, and by the small size of the deposited Ag NPs, which can produce a surface area of Ag that is suitable for the reaction with H2O2. The amperometric responses show that the limit of detection, the limit of quantification (S/N = 3) and the sensitivity are estimated to be 0.57 mu M, 1.93 mu M and 4.477 mu A mM(-1), respectively, for the linear segment. The results of the reproducibility experiments show that the use of Ag-UTPNS/GCE is feasible for the quantitative detection of certain concentration ranges of H2O2. (C) 2012 Elsevier Ltd. All rights reserved.